Effects of Inhibition of DNA Methyltransferase by 5-Azacytidine on MANF and CDNF Expression - Mukhtar, Sumeya (My University, 2020)
The role of neurotrophic factors (NTFs) in neuronal development, differentiation, neuroprotection, and maintenance is well documented. The novel family of mesencephalic astrocyte-derived neurotrophic factor (MANF) and cerebral dopamine neurotrophic factor (CDNF) have been found to protect dopaminergic neurons, providing a potential therapeutic avenue for neurodegenerative diseases. Our group has previously shown an induction of NTFs including MANF and CDNF, following treatment with valproic acid (VPA), a histone deacetylase (HDAC) inhibitor, in both cultured cells and rat brain. Furthermore, increased histone H3 acetylation was observed, indicating that epigenetic mechanisms may play a role in the modulation of MANF and CDNF. The interaction between HDAC inhibitors and DNA demethylation prompted us to investigate if DNA demethylation plays a role in the regulation of these NTFs. Treatment with 5-azacytidine (AZA; 1 – 25 µM), a potent DNA demethylating agent, for 24 hours, resulted in a significant increase in CDNF mRNA expression in rat C6 glioma cells. In the same time period, treatment with AZA resulted in a significant decrease in MANF mRNA expression. Furthermore, AZA decreased DNA methyltransferase 1 (DNMT1) mRNA and protein levels, suggesting a decrease in DNMT1 activity. Consistent with these findings, global DNA methylation was decreased following treatment with AZA. In view of the foregoing, the significant changes seen with CDNF and MANF mRNA expression following treatment with AZA, indicate that DNA demethylation may play a role in the regulation of these NTFs. These results may provide novel therapeutic approaches for neurological or related disorders and help to elucidate the mechanisms underlying the regulation of NTFs.